Proyecto de factibilidad para la creación de una caja de ahorro para los socios de la Junta de Riego La Palmira del cantón Loja - Yanza Castro, Marco Vinicio (2024)
Currently, savings banks worldwide have become a valuable source of easily accessible financing for all sectors, especially rural sectors, due to their low-interest rates, the benefits they offer for savings, and the economic boost they provide to local communities. In this context, the general objective arises of analyzing the feasibility of the savings bank for the members of the La Palmira Irrigation Board of the Loja canton who lack any nearby financial entity that helps savings or facilitates financing for their agricultural activities. To do this, descriptive, exploratory, and field research was adopted, which allowed the feasibility study to be carried out through data collection techniques such as surveys and interviews. The market study shows excellent acceptance by members, where 82% agree on creating the savings bank. The technical study defined the ideal place for the institution's implementation and the physical, technological, and human requirements necessary to begin operations. In the administrative study, a proposal was executed on the optimal structure, organization charts, and manual of functions that the savings bank must-have for proper functioning. In addition, in legal terms, the entity will be established under the provisions and regulations imposed by the regulatory and administrative entities. Finally, a financial evaluation resulted in a positive net present value (NPV), a benefit-cost ratio of 33 cents for each dollar invested, and an internal rate of return (IRR) of 51.84%. It is concluded that creating the La Palmira savings bank is feasible and can be implemented.